Pengaruh Kesadaran Merek Dalam Menentukan Niat Pelanggan Dan Perilaku Pembelian - Francis Hutabarat (Fakultas Ilmu Komputer, Universitas Klabat, 2024)
The pervasive influence and evolution of social media continue to reshape societal dynamics. Accordingly, the current study endeavors to scrutinize whether brand awareness (BA), brand knowledge (BK), and brand preference (BP) serve as independent variables influencing customer intention (CI), with Purchase Decision (PD) serving as the dependent variable with CI as mediating factor in the relationship between BA, BK, BP, and PD. Against the backdrop of the Shopee marketplace, the study was conducted through a survey targeting Shopee customers specifically generation Z or millennials who had a history of purchasing or frequent platform usage in West Java, Indonesia. The quantitative dataset was compiled from responses provided by 91 participants, employing purposive sampling technique, the collected data were subjected to Structural Equation Modeling (SEM) using SmartPLS software for analysis. The outcomes indicated that BA and BK had insignificant effects on CI and PD. Conversely, BP demonstrated a significant and positive influence on customer intention and purchase decision. Moreover, the analysis revealed that CI acts as a significant mediator between BP and purchase decision. Thus, leveraging social media can augment brand preference, with an associated increase in customer intention leading to heightened purchase decisions. These findings furnish valuable insights to businesses, aiding them in making informed decisions regarding the selection of the most suitable social media strategy.